Implementasi QRIS Metode Pembayaran Digital pada Kualitas Peningkatan UMKM di Masyarakat Desa Rancabungur - Annisa, Nabila Nur; Irwanah, Leli; Rosa, Nur Isma; Al Adawiyah, Cahya Dibah; Ranggika, Roro; Karimah, Syahadah Albaqiyatul (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2024)
QRIS is a digital payment method for the people of Rancabungur Village. In this research, researchers have interviewed 20 MSMEs about non-cash payment systems in their shops. In this research, researchers conducted outreach and registered QRIS barcodes for MSMEs. The research location was carried out in the Rancabungur Village area RW 09, 10 and 11. In collecting primary data, the researcher provided a list of questions to ask the informants. Apart from data collection techniques using interviews, researchers also used literature studies from books, journals and relevant reading sources to support this journal. Based on the results of socialization and implementation carried out by students to MSMEs. The use of QRIS for MSMEs in Rancabungur Village can change people's mindset. The use of QRIS is to emphasize the role of QRIS as a cashless payment method using only a smartphone which can make payment transactions more practical and faster.